PROPENSITY FOR FALLS IN ELDERLY FEMALE AND MALE PRACTITIONERS AND NON- PRACTITIONERS OF PHYSICAL ACTIVITIES - Guimarães, Élcio Alves; Boaventura, Cristina de Matos; Andrade, Maria Paula Pereira; Graciano, Nayara Ribeiro; Teodoro, Bárbara Vilela Franco; Lima, Kennedy Rodrigues (Manual Therapy, Posturology & Rehabilitation Journal, 2019)
Background: Aging being a natural physiological process can present both physical and psychic changes, due to the conditions of life of the person, and can be influencers for the installation of chronic non-communicable diseases, which may predispose this subject to an episode of fall. Objectives: To compare the propensity to fall in the elderly male and female, practitioners and non-practitioners of physical activities. Methods: The sample consisted of 120 elderly people of both genders practitioners and non-practitioners of physical activity and were used the “Timed Up and Go” and “Functional Reach” tests. Results: Among non-practitioners of physical activity, significant differences were observed between the values of functionality, being that the male group presented higher values than the female group, i.e., men move more, therefore has the lowest risk of fall. Conclusion: It was concluded that the female practitioners of physical activity have a greater risk of suffering an episode of fall compared to the non-practitioners, and in relation to the men practitioners and non-practitioners of physical activity there was no significant difference, showing that the elderly women have a higher risk to fall compared to the elderly men.